Poluição atmosférica no distrito de Assistência, Rio Claro/SP: reflexo do Polo Cerâmico de Santa Gertrudes/SP - Cardoso, Kaike Gregório [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The objective of this study was to analyze the impact of atmospheric pollution generated by industries of the Ceramic Pole of Santa Gertrudes (PCSG), in the district of Assistência, located in the municipality of Rio Claro/SP. Among the many environmental impacts generated by the production of floors and coverings, tiles, blocks and bricks, highlights the problem of atmospheric pollution from large amount of particulate materials that are released in all stages of the production process, including the transport of clay, main raw material of ceramic industry. To understand the meteorological dynamics in the region, were performed the collection and interpretation of data regarding temperature, relative humidity, precipitation, atmospheric pressure, direction and speed of winds, from January 2016 to July 2017, obtained in the Meteorological Station of the Center for Analysis and Environmental Planning (CEAPLA) of UNESP, Campus of Rio Claro. The data relating to the concentration of coarse particulate material (MP10), covering the same period, were collected at the Station for Monitoring of Air Quality in Santa Gertrudes and collected through the System of Information of Air Quality (QUALAR) of the Company Environmental of State of São Paulo (CETESB). The literature review, identification and study of the particles released in all production process, associated to the understanding of the local meteorological dynamics, allowed the identification of the areas most impacted by the particulate material in the district of Assistência. Thus, the results obtained in this research can serve as a basis for public administrators, with a view to taking measures to reduce the air pollution that reaches the study area, aiming to improve the quality of life of the residents of Assistência

O objetivo deste trabalho foi analisar o impacto da poluição atmosférica, gerada pelas indústrias do Polo Cerâmico de Santa Gertrudes (PCSG), sobre o distrito de Assistência, situado no município de Rio Claro/SP. Dentre os inúmeros impactos ambientais gerados pela produção de pisos e revestimentos, telhas, blocos e tijolos, destaca-se o problema da poluição atmosférica oriunda da grande quantidade de materiais particulados que são liberados em todas as etapas do processo produtivo, incluindo o transporte de argila, principal matéria-prima do setor cerâmico. Para compreensão da dinâmica meteorológica da região, efetuou-se a coleta e interpretação dos dados referentes à temperatura, umidade relativa, precipitação total, pressão atmosférica, direção e velocidade dos ventos, de janeiro de 2016 a julho de 2017, obtidos na Estação Meteorológica do Centro de Análise e Planejamento Ambiental (CEAPLA), da UNESP, Câmpus de Rio Claro. Os dados referentes à concentração de material particulado grosseiro (MP10), abrangendo o mesmo período, foram coletados na Estação de Monitoramento da Qualidade do Ar de Santa Gertrudes e coletados através do Sistema de Informações da Qualidade do Ar (QUALAR) da Companhia Ambiental do Estado de São Paulo (CETESB). A revisão bibliográfica, identificação e estudo das partículas liberadas em todo processo produtivo, associada à compreensão da dinâmica meteorológica local, permitiram a identificação das áreas mais impactadas pelo material particulado no distrito de Assistência. Assim, os resultados obtidos nessa pesquisa poderão servir de base aos administradores públicos, a fim de tomar medidas para amenizar a poluição atmosférica que atinge a área de estudo, visando melhorar a qualidade de vida dos moradores de Assistência
Keywords: Ar - Poluição; Geografia urbana; Ceramica - Industria; Material cerâmico; Rio Claro (SP); Santa Gertrudes (SP); Assistência (Rio Claro, SP)